2023
DOI: 10.1186/s12870-023-04312-w
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimizing concentration of exogenous application of γ-aminobutyric acid on NaCl-stressed pineapple mint (Mentha suaveolens) using response surface methodology: an investigation into secondary metabolites and physiological parameters

Abstract: Salinity, a severe worldwide issue, compromises the economic production of medicinal plants including mints and causes drug-yield decline. γ-Aminobutyric acid (GABA) is a tolerance-inducing signaling bio-molecule in various plant physiological processes. Pineapple mint (Mentha suaveolens Ehrh.) is a valuable medicinal herb with an exhilarating scent of citrus fruit. Piperitenone oxide is the major bioactive constituent of its essential oil, having significant demand by pharmaceutical industries. Nonetheless, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Following the optimized method for quantification of EOs in our previous studies [ 40 41 , 57 ], GC-MS (Agilent 5977 A) and GC-FID (Agilent 7990B) analysis of 24 samples (4 phenological stage × 2 genotype × 3 rep) was performed utilizing an HP-5MS capillary column (5% phenylmethyl polysiloxane, 30 m length, 0.25 mm internal diameter, 0.1 μm film thickness). EO samples were diluted with n -hexane (1:100), after which an aliquot of 1 µL was injected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the optimized method for quantification of EOs in our previous studies [ 40 41 , 57 ], GC-MS (Agilent 5977 A) and GC-FID (Agilent 7990B) analysis of 24 samples (4 phenological stage × 2 genotype × 3 rep) was performed utilizing an HP-5MS capillary column (5% phenylmethyl polysiloxane, 30 m length, 0.25 mm internal diameter, 0.1 μm film thickness). EO samples were diluted with n -hexane (1:100), after which an aliquot of 1 µL was injected.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the identity of some constituents was reconfirmed by peak assignment of certified reference standards (thymol, carvacrol, caryophyllene oxide, carvacrol methyl ether, and γ-terpinene, Supleco, USA). The content of each EO compound was expressed as relative percentage of that constituent [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…A large number of studies have shown that when plants are subjected to stresses (both abiotic and biotic) such as hypoxia, drought, cold, heat, salt, ultraviolet, heavy metals, mechanical damage, and diseases and pests, GABA can rapidly accumulate to maintain the equilibrium of redox, cytoplasmic pH, osmotic potential, and C/N content in the cells to ensure their normal physiological metabolism under adverse conditions and alleviate the extent of damage caused by these stresses (Seifikalhor et al, 2019;Li et al, 2020;Abd Elbar et al, 2021;Mishra et al, 2023;Ullah et al, 2023). The exogenous application of GABA can improve the stress resistance of plants and promote their growth under stress by increasing stomatal conductance, improving the activities of antioxidant enzymes, promoting the production of stress-response amino acids and polyamines, and regulating the metabolism of organic acids among others (Jin et al, 2019;Wang et al, 2022;Ahmadi et al, 2023). Although numerous studies have identified the contribution of GABA to plant growth and development under different stress conditions and the underlying mechanisms of GABA actions, the effects of exogenous GABA on the growth of the in vitro plantlets under the extreme artificial conditions of tissue culture and the related molecular mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%